Effect of Phase Feeding Supplemental Fungus Myceliated Grain on Oocyst Excretion and Performance of Broiler Chickens - Willis, W.L.; Isikhuemhen, O.S.; Hurley, S.; Ohimain, E.I. (International Journal of Poultry Science, 2010)
An experiment was conducted to investigate Fungus Myceliated Grain (FMG) feed inclusion strategies for broilers and the effects of this feed on natural Eimeria oocyst excretion and bird performance. Two hundred ninety-four straight-run day-of-hatch broiler chicks were obtained from a local commercial hatchery and randomly distributed in seven treatment groups with three replications of 14 chicks as follows: 1) Control-No FMG; 2) 5% FMG-starter feed; 3) 5% FMG-grower feed; 4) 5% FMG-starter, grower, finisher feed; 5) 10% FMG-starter feed; 6) 10% FMG-grower feed and 7) 10% FMG starter, grower, finisher feed. Fecal oocyst count, mortality, live body and bursa weight were determined at the end of the 7 wk trial. Results showed that broilers in treatments 1 and 2 produced the highest counts of Eimeria, which was significantly higher than that of treatment 6 (p<0.05) with the lowest count of Eimeria. Mortality was not significantly influenced by treatments. There were significant differences in the live and bursa weights, but not in the relative bursa percent. The results suggest the best response in terms of anticoccidial protection occurs with the 10% inclusion in the growers feed and for body weight at the 5% inclusion level in the starter feed.